Humana conditio and virtual intersubjectivity (Devenires, 2012)
This article examines certain anthropological-philosophical considerations of the concept of the human condition on the basis of current modes of social action and intersubjective relations mediated by remote electronic technologies. To this end it takes up the notion of vita activa formulated by Hannah Arendt in the modern context of our labor, work and action through recently developed communication networks; webs that have introduced new social, political, sexual and intercultural conditionings that must be reflected upon prudently, since these technological circumstances remit us collaterally to the problem of the generalized “dismodernization” of our social and political formations that has left the institutions and rights achieved by the citizenry unprotected. The aim is to rethink the possibility of reversing –ethically and politically– the growing presence of a worldwide network of simulation that offers us an anonymous audiovisual environment devoid of human rostrums.